FINITE ELEMENT ANALYSES OF GROUND DEFORMATION CAUSED BY RECTANGULAR PIPE ROOFING AND SHIELD TUNNELLING SUPPORT - MOHD NASIR, MUHAMMAD YUSOFF (2020)
Trough width parameter, K found from the literature mostly were designed for circular shape tunnel and estimation of inflection point, i for rectangular tunnel is yet to be identified by any researcher. Generally, the aim of the study is to do a research on the value of i induce by rectangular tunnel to be constructed using FEM analysis. To be specified, the objectives of the study are to compare the Mohr-Coulomb and Hardening Soil model in FEM analysis, followed by an investigation on the soil parameter that effect significantly to the shield and pipe roof support respectively for rectangular tunnel through parametric study, and lastly to develop a design chart of i value for rectangular tunnel through parametric study which comprising variation of tunnel size ratios using numerical analyses.